Homestay owners' perspective of economic sustainability of the registered Malaysian homestay - Balasingam, Ann Selvaranee; Bojei, Jamil (Universiti Putra Malaysia Press, 2019)
The main economic issues faced by the registered Malaysian homestay program are the issues of competition from unregistered homestays, local community employment and the tourism multiplier effect of homestays. This research investigates the relationship between destination competitiveness, employment and multiplier effect and homestay sustainability from the homestay owners' perspective. The objective of this study is to measure homestay sustainability using destination competitiveness, employment, and the multiplier effect. Survey questionnaires were given to the 254 homestay owners using cluster sampling method. To analyze the data, Partial Least Square (PLS) approach to Structural Equation Modeling (SEM) was used. The findings of this study confirm the significant relationships between destination competitiveness and multiplier effect with homestay sustainability. The most important finding is that the homestay owner confirms that the unregistered homestays are not a threat to the competitiveness of the registered homestay program. Secondly, registered homestays do have the multiplier effect and provide a steady financial overflow to the homeowners' and the other stakeholders within the local community. The findings also suggest no significant relationship between employment and homestay sustainability.